The effects of small-sided games on physical fitness in basketball players: a systematic review and meta-analysis - Zhang, Z.; Xu, J.; Ji, X.; Chen, R. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background As a type of game-based training (GBT), small-sided games (SSGs) are often compared with non-game-based training (NGBT) in team sports. However, there is still no consensus on the chronic effects between SSGs and NGBT, including high intensity interval training (HIIT) and traditional technical drills (TTD), on physical performance in basketball players.